Preliminary Screening of Phytochemical Compounds of Jeriangau (Acorus calamus) from West Sumatra - Refa Rahmaddiansyah; Muhammad Abi Ghoffari Siregar; Rauza Sukma Rita (Majalah Kedokteran Andalas, 2023)
Indonesia's biodiversity is able to meet the needs of human life in various sectors, especially in the utilization of potential plants. Jeriangau (Acorus calamus) is a rhizome plant that is widely used as traditional medicine in various ethnicities, especially in West Sumatra. This is because jeriangau contains bioactive compounds that have the potential to treat various diseases. This research method is an experimental study to qualitatively confirm the bioactive components contained in the rhizome of Jeriangau. The test results of jeriangau simplicia samples showed positive results for the active group of secondary metabolites of flavonoids, tannins, and saponins which have potential as antioxidants. Flavonoids can reduce the risk of chronic disease, especially cardiovascular disease and cancer. Tannins have antioxidant properties and can protect the skin from damage caused by UV radiation. Saponins are known to act as antiviral, antimicrobial, and anti-inflammatory. Therefore, Acorus calamus extract can be used as an antibacterial, antiviral, antiseptic, antifungal, and acts as an antioxidant. Further research is needed on studies of inflammatory activity, either in vitro, in vivo, or in human treatment.Keywords: jeriangau; phytochemicals; West Sumatra; antioxidant.